Health sciences educators’ and educator candidates’ digipedagogical competence: assessment after an online course - Saaranen Terhi; Kiikeri Janette; Salminen Leena; Kokkonen Kukka-Maaria; Elonen Imane; Ryhtä Iina; Mikkonen Kristina; Kääriäinen Maria; Sjögren Tuulikki; Korpi Hilkka; Sormunen Marjorita (Italy, 2022)
The purpose of this paper is to describe the implementation of an online course, as well its development after implementation, and to focus on the health sciences educators’ and educator candidates’ assessments of their digipedagogical competence after the course. Semi-structured interviews to learners (n = 11) were used to collect data that were then analysed using inductive content analysis. The learners perceived that their ability to exploit digital applications increased and that they critically reflected upon their use of digital technology in teaching. The feedback from and presence of the tutors, as well as the collaborative activities with peer learners in the course, were generally regarded positively. Suggestions for improving the course were to limit the course content and to increase communality and other factors that support learners’ learning and work. The lessons learned from this study can be applied in basic and continuing professional development of health sciences educators.